siRNA Treatments for Diabetic Neuropathy: Obstacles and Delivery Techniques - Akhtar, Mohammad Shabib; Mohsin, Nehal; Zahak, Ahmad; Ahmed, Khalid Altigani Awad Alkarem; Alhazmi, Yasir; Taleuzzaman, Mohamad (Current Molecular Medicine, 2025)
Targeting genes using siRNA shows promise as an approach to alleviate symptoms of diabetic neuropathy. It focuses on neuropathies and distal symmetric polyneuropathy (DSPN) to explore the potential use of small interfering RNA (siRNA) as a treatment for diabetic neuropathy. Timely identification and management of neuropathy play a critical role in mitigating potential complications. RNAi success depends on understanding factors affecting small interfering RNA (siRNA) functionality and specificity. These include sequence space restrictions, structural and sequence features, mechanisms for nonspecific gene modulation, and chemical modifications. Addressing these factors enhances siRNA performance for efficient gene silencing and confidence in RNAi-mediated genomic studies. Diabetic retinopathy, particularly in South Asian, African, Latin American, and indigenous populations, is a significant concern due to its association with diabetes. Ethnicity plays a crucial role in its development and progression. Despite declining rates in the US, global trends remain concerning, and further research is needed to understand regional differences and reinforce ethnicity-based screening and treatment protocols. In this regard, siRNA emerges as a valuable instrument for early intervention strategies. While presenting promising therapeutic applications, siRNA utilization encounters challenges within insect pest control contexts, thereby providing insights into enhancing its delivery mechanisms for neuropathy treatment purposes. Recent advancements in delivery modalities, such as nanoparticles, allow for the controlled release of siRNA. More investigation is necessary to grasp the safety and efficacy of siRNA technology fully. It holds promise in transforming the treatment of diabetic neuropathy by honing in on particular genes and tackling issues such as inflammation and oxidative stress. Continuous advancements in delivery techniques have the potential to enhance patient results significantly. SiRNA targets genes in diabetic neuropathy, curbing nerve damage and pain and potentially preventing or delaying the condition. Customized treatments based on genetic variations hold promise for symptom management and enhancing quality of life.
Keywords: Small interfering RNA (siRNA)